IgG, IgM and IgA antibody response for the diagnosis and follow-up of paracoccidioidomycosis: Comparison of counterimmunoelectrophoresis and complement fixation - Bueno, J. P.; Mendes-Giannini, Maria José Soares [UNESP]; Del Negro, G. M. B.; Assis, C. M.; Takiguti, C. K.; Shikanai-Yasuda, M. A. (Oxford University Press (OUP), 1997)
IgG, IgM and IgA antibodies to GP43 (glycoprotein fraction of Paracoccidioides brasiliensis) were measured by ELISA in 63 samples from 23 patients with paracoccidioidomycosis before and twice after chemotherapy was started. Antibodies against P. brasiliensis were detected by indirect immunofluorescence (IF) (IgG, IgM and IgA isotypes), counterimmunoelectrophoresis (CIE) and complement fixation. Two control groups composed of 19 healthy individuals and 12 patients with other diseases (six with histoplasmosis, three with tuberculosis and three with other mycoses). The highest efficiency percentages were found with IgG and IgA- ELISA (100%), IgG-IF (96.2%), CIE (94.4%) and the lowest with CF (75.9%). Highest positive and negative predictive values (100%) were observed for IgG and IgA ELISA. IgG and IgM-ELISA antibodies are more often found in patients with acute than chronic disease (P = 0.01). Four to six months after treatment follow-up showed decreased levels of IgG and IgM-ELISA for acute cases and decreased titres of CIE for chronic cases in relation to pretreatment levels. This study suggests that IgG-ELISA anti-GP43 represents a good marker to monitor clinical response to therapy.
Keywords: Diagnosis; ELISA anti-GP43; P. brasiliensis; Paracoccidioidomycosis; glycoprotein; immunoglobulin a antibody; immunoglobulin g antibody; immunoglobulin m antibody; antibody response; biopsy; complement fixation; controlled study; counter immunoelectrophoresis; enzyme linked immunosorbent assay; follow up; fungus identification; histoplasma capsulatum; human; immunofluorescence; major clinical study; paracoccidioides brasiliensis; south american blastomycosis; sputum analysis; Acute Disease; Antibodies, Fungal; Antibody Formation; Antifungal Agents; Chronic Disease; Complement Fixation Tests; Counterimmunoelectrophoresis; Enzyme-Linked Immunosorbent Assay; Fluorescent Antibody Technique, Indirect; Humans; Immunoglobulin A; Immunoglobulin G; Immunoglobulin M; Reference Values; Ajellomyces capsulatus; Fungi; Paracoccidioides brasiliensis; paracoccidioidomycosis brasiliensis